Techno-economic assessment of benzyl benzoate clean production using conventional heating or microwaves - Aprile, Simona; Venturi, Valentina; Presini, Francesco; Mustafa, Ahmad; Sadek, M. Shaaban; Inayat, Abrar; Remonatto, Daniela [UNESP]; Giovannini, Pier Paolo; Lerin, Lindomar Alberto (Elsevier, 2023)
Benzyl benzoate is an important anti-scabies agent, so finding sustainable production processes is essential. This work involved the techno-economic assessment of benzyl benzoate production in a solventless system with conventional heating or microwave-assisted. The proposed processes' conditions were optimized by transesterifying methyl benzoate and benzyl alcohol in a solventless system using the Lipozyme 435 lipase as the catalyst. The optimized conditions were an ester/alcohol molar ratio of 1:6, a temperature of 73 °C, and enzyme loading of 10% and 16% (w/w), for conventional heating and microwave-assisted, respectively. Under these conditions, the two reactions reached conversions greater than 90% in 24 h and 82% in 7 h. The tests on lipase reusability showed that the ester production remains stable for up to 4 use cycles. Gas chromatography and proton NMR confirmed that benzyl benzoate could be produced biocatalytically, and a high purity can be obtained by simple distillation. The economic analysis of the process showed that the total capital investment was favorable, suggesting a promising investment opportunity. Furthermore, a production total cost showed a favorable positive net present value and returned on investment for benzyl benzoate production. Hence, the proposed clean production of benzyl benzoate can be considered for industrial scale-up.